2019
DOI: 10.1158/2326-6066.cir-18-0504
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Expression Is Enhanced by T-cell Receptor Stimulation Strength and Correlates with Improved Tumor Control in Melanoma

Abstract: microRNAs are short noncoding RNAs that regulate protein expression posttranscriptionally. We previously showed that miR-155 promotes effector CD8 þ T-cell responses. However, little is known about the regulation of miR-155 expression. Here, we report that antigen affinity and dose determine miR-155 expression in CD8 þ T cells. In B16 tumors expressing a low-affinity antigen ligand, tumorspecific infiltrating CD8 þ T cells showed variable miR-155 expression, whereby high miR-155 expression was associated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…We and others had previously shown that the upregulation of the endogenous miR-155 is proportional to the affinity of the TCR to the peptide:MHC ligand, both in mouse and human CD8 + T cells. 8,36,45 Together, these observations suggest that overexpressing miR-155 in low-affinity T cells would selectively support their activation and effector functions, as they are the ones with the lowest natural miR-155 increase upon antigen activation. Indeed, we demonstrated that OT-1 cells stimulated with the N4 peptide upregulated miR-155 to a higher level compared to OT-1 cells stimulation with the T4 peptide.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We and others had previously shown that the upregulation of the endogenous miR-155 is proportional to the affinity of the TCR to the peptide:MHC ligand, both in mouse and human CD8 + T cells. 8,36,45 Together, these observations suggest that overexpressing miR-155 in low-affinity T cells would selectively support their activation and effector functions, as they are the ones with the lowest natural miR-155 increase upon antigen activation. Indeed, we demonstrated that OT-1 cells stimulated with the N4 peptide upregulated miR-155 to a higher level compared to OT-1 cells stimulation with the T4 peptide.…”
Section: Discussionmentioning
confidence: 90%
“…This hypothesis was indeed supported by our observation that miR-155 is less upregulated in low-affinity T cells. 36 Thus, this observation would suggest that forced miR-155 overexpression may have more impact in a low-affinity T cell response.…”
Section: Overexpression Of Mir-155 In Ot-1 Cells Improves Their Abilimentioning
confidence: 87%
“…They measured miR-155 expression in CD8 T cells isolated from tumor-infiltrating lymph nodes and tumor tissue samples from melanoma patients and murine models. miR-155 expression in CD8 T cells was found to depend on antigen stimulation [56]. Previous investigations had shown that TCR (T Cell Receptor) is responsible for NF-kB and AP1 activation that in turn, upregulates miR-155 expression [65,66].…”
Section: The Advent Of Immune Checkpoint Inhibitors: Do Mirnas Have Amentioning
confidence: 99%
“…Moreover, the expression of miR-155 is stimulated by IRF4, which is overexpressed in CD8 T cells from Murine lymphocytic choriomeningitis virus chronic infection [55]. Thus, Martinez-Usatorre and colleagues concluded that miR-155 could be considered a marker of responsiveness of CD8 T cells, as further demonstrated by its upregulation after PD1 blockade [56].…”
Section: The Advent Of Immune Checkpoint Inhibitors: Do Mirnas Have Amentioning
confidence: 99%
See 1 more Smart Citation